Factors Predicting Cybersex Use and Difficulties in Forming Intimate Relationships among Male and Female Users of Cybersex - Weinstein, Aviv M.; Zolek, Rinat; Babkin, Anna; Cohen, Koby; Lejoyeux, Michel (Frontiers in Psychiatry, 2015)
Sexual addiction otherwise known as compulsive sexual behavior is associated with serious psychosocial problems and risk-taking behavior. This study used the Cybersex addiction test, Craving for pornography questionnaire and a Questionnaire on intimacy among 267 participants (197 males and 75 females) mean age for males 28.16 (s.d= 6.8) and for females 25.5 (s.d= 5.13) who were recruited from special sites that are dedicated to pornography and cybersex on the internet. Results of regression analysis indicated that pornography, gender and cybersex significantly predicted difficulties in intimacy and it accounted for 66.1% of the variance of rating on the intimacy questionnaire. Secondly, regression analysis also indicated that craving for pornography, gender, and difficulties in forming intimate relationships significantly predicted frequency of cybersex use and it accounted for 83.7% of the variance in ratings of cybersex use. Thirdly, men had higher scores of frequency of using cybersex than women [t (2,224) = 1.97, p<0.05] and higher scores of craving for pornography than women [t (2,265) = 3.26, p<0.01] and higher scores on the questionnaire measuring difficulties in forming intimate relationship than women [t (2,224) = 1.97, p<0.05]. These findings support previous evidence for sex differences in compulsive sexual behavior.